Six Versus 12 Months of Dual Antiplatelet Therapy After Implantation of Biodegradable Polymer Sirolimus-Eluting Stent: Randomized Substudy of the I-LOVE-IT 2 Trial. (February 2016) - Han, Yaling; Xu, Bo; Xu, Kai; Guan, Changdong; Jing, Quanmin; Zheng, Qiangsun; Li, Xueqi; Zhao, Xianxian; Wang, Haichang; Zhao, Xuezhong; Li, Xiaoyan; Yu, Pengfei; et al.
Abstract : Background—: There are no reports on a large-scale randomized trial exploring optimal dual antiplatelet therapy (DAPT) duration after biodegradable polymer sirolimus-eluting stent implantation. We sought to report the outcomes of a randomized substudy of the prospective Evaluate Safety and Effectiveness of the Tivoli DES and the Firebird DES for Treatment of Coronary Revascularization (I-LOVE-IT 2) trial. Methods and Results—: In the prospective noninferiority randomized I-LOVE-IT 2 trial, 1829 patients allocated to the biodegradable polymer sirolimus-eluting stent group were also randomized to receive either 6-month (n=909) or 12-month DAPT (n=920). The primary end points of this noninferiority substudy were 12-month target lesion failure (composite of cardiac death, target vessel myocardial infarction or clinically indicated target lesion revascularization), and the major secondary end points were 12-month net adverse clinical and cerebral events (composite of all-cause death, all myocardial infarction, stroke, or major bleeding [Bleeding Academic Research Consortium type ≥3]). The 12-month target lesion failure in 6-month DAPT group was comparable with the 12-month DAPT group (6.8% versus 5.9%; difference and 95% confidence interval, 0.87% [−1.37% to 3.11%], P for noninferiority=0.0065). Further follow-up at 18 months showed that incidence of target lesion failure and net adverse clinical and cerebral events were similar between the 2 groups (7.5% versus 6.3%, log-rank P =0.32; 7.8% versus 7.3%, log-rank P =0.60; respectively), as well as their individual end point components. Conclusions—: This study indicated noninferiority in safety and efficacy of 6-month versus 12-month DAPT after implantation of a novel biodegradable polymer sirolimus-eluting stent. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01681381. Abstract : Supplemental Digital Content is available in the text.